Surgical Approaches Based on Biological Objectives: GTR versus GBR Techniques - Gaia Pellegrini; Giorgio Pagni; Giulio Rasperini (Hindawi Limited, 2013)
Guided tissue regenerative (GTR) therapies are performed to regenerate the previously lost tooth supporting structure, thus maintaining the aesthetics and masticatory function of the available dentition. Alveolar ridge augmentation procedures (GBR) intend to regain the alveolar bone lost following tooth extraction and/or periodontal disease. Several biomaterials and surgical approaches have been proposed. In this paper we report biomaterials and surgical techniques used for periodontal and bone regenerative procedures. Particular attention will be adopted to highlight the biological basis for the different therapeutic approaches.